THE ROLE OF BIG FIVE PERSONALITY TRAITS IN PREDICTING PROSPECTIVE EFL TEACHERS' ACADEMIC ACHIEVEMENT - Şenay Kırkağaç; Hüseyin Öz (Informascope, 2017)
This study sought to find out the possible relationships between personality traits and academic achievement of prospective English as a Foreign Language (EFL) teachers. A total of 200 university students from a major state university voluntarily participated in the study. Data were collected through the International Personality Item Tool (IPIP) and the self-reported grade-point average (GPA). The tool was designed to determine the dominant personality trait(s) of the participants within the scope of Big Five Personality Traits; that is, conscientiousness, extraversion, agreeableness, openness and neuroticism. In line with the literature the results revealed that there were statistically significant relationships between the participants' personality traits and academic achievement. Specifically, conscientiousness, openness and agreeableness were the personality traits that positively and significantly correlated with academic achievement. Furthermore, in order to find out the predictive effects of the personality traits on academic achievement, the multiple regression analyses were conducted. According to the results of the analyses, personality traits were able to predict 17% of the academic achievement, with openness being the strongest determinant. Conscientiousness followed openness while three other traits failed to predict academic achievement of the participants.